Sinantropia e análise da variação espacial do índice por Nuorteva (1963) em dípteros muscóides no município do Rio de Janeiro, RJ, Brasil - Sordillo, Claudia Maria de Oliveira (1991)
The objectives of the study were to estimate the synanthropic index (proposed by Nuorteva, 1963) of the most abundant Calliphoridae, Faniidae, Muscidae and Sarcophagidae species captured in the city of Rio de Janeiro, RJ, Brasil, during seven months (setember 1988 till March 1989), and to observe the variation of this index while doing collections in different points of the urban area. Beside the synanthropy index, the monthly variation in the occurrence of the most abundant species was also analyzed (total number of belongings collected n. = 30, from the families mentioned in the urban area: the frequency with which they were captured in each of the collection tales and preference of larvae and adults for one or more of the four types of baits used (raw fish. human feces, bovine liver and chicken gizzards). According to the results obtained, it was observed that most of the studied species showed a variation in Its synanthropic index, it was also found that the most synanthropic species have a cosmooplite distribution, while the most asynanthropic species are Neotropical.